Oscillon lifetime in the presence of quantum fluctuations - Saffin, Paul M.; Tognarelli, Paul; Tranberg, Anders (Springer, 2014)
We consider the stability of oscillons in 2+1 space-time dimensions, in the presence of quantum fluctuations. Taking the oscillon to be the inhomogeneous mean field of a self-interacting quantum scalar field, we compare its classical evolution to the evolution in the presence of quantum fluctuations. The evolution of these and their back reaction onto the mean field is implemented through the inhomogeneous Hartree approximation, in turn computed as a statistical ensemble of field realizations. We find that although the lifetime of the oscillon is dramatically reduced compared to the classical limit, the regions of longevity are similar in the space of Gaussian initial configurations.